Pengaruh Kecemasan terhadap Peningkatan Kadar Gula Darah Sewaktu Pasien Diabetes Melitus Tipe II RS. Dr. Moewardi - Nina Widyarini, Yosephine; Nugroho, I. G. B. Indro; Hidayati, H, Rosalia Sri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Diabetes Mellitus is caused by increasing of blood glucose levels due to lack of insulin hormone both absolute and relative. High blood glucose levels in patient with Diabetes Mellitus can caused by 5 factors such as enzym, hormone, gastrointestinal system, anxiety, and carbohydrate intake. Patient with high tension is estimated to have a worse prognosis than patient without any tension. This research aims to know how significant the effect of tension to increasing of blood glucose levels. Method: This study was a descriptive analytical research using cross sectional approach implemented in March 2012 at internal medicine clinic of RS. Dr. Moewardi Surakarta. The sample was taken using purposive sampling and random sampling after being selected based on the inclusion and exclusion criteria. The subject filled in (1) curriculum vitae form, (2) L-MMPI questionnaire to find out the respondentâs truthfulness in filling in questionnaire, (3) Zung questionnaire to find out the anxiety score and checking for blood glucose. 60 subject of research were obtained as the data and analyzed using Independent Sample t-test and linear regression analysis test through SPSS 17.00 for windows program. Result: Significance values that indicated on independent sample t-test is 0.00, it can be concluded that the data are significantly different. Linear regression analysis test obtained the equation that Y=a+Bx = 49.89 + 3.09 X, which indicates if there is an increased level of anxiety, then the blood glucose levels will rise as much as 49.89 + 3.09 X unit. Conclusion: Blood glucose level in patient Diabetes Mellitus Type II with anxiety is higher than patient without anxiety and the effect of anxiety to increasing blood glucose levels is still weak. Keywords : Diabetes Mellitus Type II, Blood Glucose Level, Anxiety